Genotyping SSR length variants by isothermal DNA amplification - Lee, David; Ialicicco, Manuela; Akkinepalli, Harika; Morreale, Giacomo; Liu, Yan; Leung, Hei; Scippa, Gabriella S.; Greenland, Andy; Mackay, Ian (Canadian Science Publishing, 2012)
Loop-mediated isothermal DNA amplification (LAMP) is an alternative method for the amplification of DNA sequences. It has been applied primarily for the detection of specific targets. We demonstrate the novel use of LAMP to amplify SSR alleles in a set of rice varieties and show the results to be consistent with analysis performed by PCR. Furthermore, we test the sensitivity of the assay and show it to amplify from near single copy target.